Yayasan UMP Sulung Scholarship especially for B40 students - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
BATU PAHAT, 17 February 2022 - The only child or first child in a B40 family who successfully pursues study in the university and is offered to study at Universiti Malaysia Pahang (UMP) to pursue a diploma and bachelor’s degree program has the opportunity to receive the Sulung Scholarship under Yayasan UMP.